Local visual perception bias in children with high-functioning autism spectrum disorders; do we have the whole picture?. (3rd March 2016) - Falkmer, Marita; Black, Melissa; Tang, Julia; Fitzgerald, Patrick; Girdler, Sonya; Leung, Denise; Ordqvist, Anna; Tan, Tele; Jahan, Ishrat; Falkmer, Torbjorn
Abstract: Objective : While local bias in visual processing in children with autism spectrum disorders (ASD) has been reported to result in difficulties in recognizing faces and facially expressed emotions, but superior ability in disembedding figures, associations between these abilities within a group of children with and without ASD have not been explored. Methods : Possible associations in performance on the Visual Perception Skills Figure–Ground test, a face recognition test and an emotion recognition test were investigated within 25 8–12-years-old children with high-functioning autism/Asperger syndrome, and in comparison to 33 typically developing children. Results : Analyses indicated a weak positive correlation between accuracy in Figure–Ground recognition and emotion recognition. No other correlation estimates were significant. Conclusion : These findings challenge both the enhanced perceptual function hypothesis and the weak central coherence hypothesis, and accentuate the importance of further scrutinizing the existance and nature of local visual bias in ASD.